The advent of chimeric antigen receptor T Cell therapy in recalibrating immune balance for rheumatic autoimmune disease treatment - Guo, Qianyu; Li, Jie; Wang, Juanjuan; Li, Linxin; Wei, Jia; Zhang, Liyun (Frontiers in Pharmacology, 2024)
CAR-T cell therapy, a cutting-edge cellular immunotherapy with demonstrated efficacy in treating hematologic malignancies, also exhibits significant promise for addressing autoimmune diseases. This innovative therapeutic approach holds promise for achieving long-term remission in autoimmune diseases, potentially offering significant benefits to affected patients. Current targets under investigation for the treatment of these conditions include CD19, CD20, and BCMA, among others. However, CAR-T therapy faces difficulties such as time-consuming cell manufacturing, complex and expensive process, and the possibility of severe adverse reactions complicating the treatment, etc. This article examines CAR-T therapy across various rheumatic autoimmune diseases, including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), Sjögren’s syndrome (SS), systemic sclerosis (SSc), antisynthetase syndrome (ASS), and ANCA-associated vasculitis (AAV), highlighting both therapeutic advancements and ongoing challenges.